Development of Carabisatulus Chatbot Learning Media Based on Environment to Improve Science Learning Outcomes - Berlian Hariratul Mahya; Deni Setiawan (Jurnal Penelitian Pendidikan IPA, 2024)
According to the results of observations conducted by researchers at SD Negeri Bakalrejo 1, problems were found in the form of limited learning media and student learning outcomes which were still in the low category in science subject content. Based on this problem, the researcher aims to develop, test the feasibility and test the effectiveness of the environment-based Carabisatulus chatbot learning media on the learning outcomes of class V students at SD Negeri Bakalrejo 1, especially on science lesson content. The type of research used is research and development (RnD) using the Borg and Gall model which was modified into 9 stages. Data collection through observation, interviews, questionnaires and documentation. The results of the product assessment are validation of learning media carried out by experts in the field of materials and media with a percentage of 92.5% and 95% with a classification of "very feasible". Media effectiveness using the T test obtained a significance value of 0.000. The results of the N-gain calculation found a value of 0.6641 with "medium" criteria. So the environment-based Carabisatulus chatbot learning media can be said to be very feasible and effective to apply in improving student learning outcomes. Researchers recommend always developing digital-based learning media and maximizing existing applications to encourage educational progress in Indonesia.